The Influence of Perceived Ease of Use and Brand Trust on the Behavioral Intention to Use Digital Wallet GoPay in Surabaya City - Zulfansyah, Mohammad Kahfi; Dermawan, Rizky (Indonesian Journal of Business Analytics, 2024)
This study aims to determine the influence of Perceived Ease of Use and Brand Trust on Behavioral Intention to Use Digital Wallet GoPay in Surabaya City. This study used a quantitative methods with a sample of 100 respondents using non-probability sampling techniques with purposive sampling methods. The population used in this study is Surabaya residents who have used the GoPay digital wallet service. This research is expected to contribute         solving the problem of GoPay Behavioral Intention to Use. The analysis technique  used in  this  study  is the Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study indicate that the influence of Perceived Ease of Use and Brand Trust on Behavioral Intention to Use. Based on the results of the hypothesis test, it was concluded that Perceived Ease of Use and Brand Trust has a significant effect on Behavioral Intention to Use.